Cloud Computing's Killer App Gaming. - Ross, P.E (IEEE spectrum)
In recognition of the huge importance of graphics and gaming to the future of computing, Advanced Micro Devices (AMD), of Sunnyvale, Calif., is building the fastest commercial supercomputer in the world and selling its use to makers of online games. When it's ready, in the second half of 2009, it will manage a thousand million million floating-point operations per second-a petaflop. That will put it on a par with Roadrunner, the U.S. Department of Energy's most powerful machine.